IMPLEMENTASI PROGRAM GERBANGDESSIGOT (GERAKAN MEMBANGUN DESA SISTEM GOTONG ROYONG) DI DESA BELANTIH KECAMATAN KINTAMANI KABUPATEN BANGLI - Utami Dewi, Ni Nyoman Sri; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT Program Gerakan Membangun Desa Sistem Gotong Royong (Gerbangdessigot) is a program from Bangli District Govement in an effort to accelerate village development. The gerbangdessigot program has been implemented in Bangli District in 2010. The purpose of this study was to find out more about the Implementationn of the Program Gerbangdesisigot (Gerakan Membangun Desa Sistem Gotong Royong) in Belantih Village, Kintamani Sub-District, Bangli District. The theory used in this study is the theory of implementation by Merilee S. Grindle, which includes content of policy and context of policy. This study uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The results of this study are that the implementatioon Program Gerakan Membangun Desa Sistem Gotong Royong (GERBANGDESSIGOT) has not been effective because there are two problems, namely the priority of using funds budgeted to strengthen BUMDES capital and women's empowerment not being effective. Keywords: Implementation, Gerbangdessigot Program, Belantih Village